Differences Between High‐ and Low‐Motility Buffalo Sperm Identified by Comparative Proteomics. Issue 3 (22nd March 2015) - Huang, Y‐L; Fu, Q; Yang, L; Guan, J‐L; Pan, H; Chen, F‐M; Lu, K‐L; Zhang, M
Contents: This study was undertaken to investigate differences in protein expression between high‐ and low‐motility sperm of swamp buffalo. The research used two‐dimensional gel electrophoresis (2DE) coupled to matrix‐assisted laser desorption/ionization time‐of‐flight tandem mass spectrometry (MALDI‐TOF/TOF‐MS) to analyse the different proteins. The results showed 18 different expression protein spots between high‐ and low‐motility buffalo sperm; eight of these proteins were up‐regulated in low‐motility sperm, five were down‐regulated, one deleted and four proteins specifically expressed. Finally, four proteins were successfully identified by MS as belonging to three unique proteins; they are outer dense fibre of sperm tails protein 2 (ODF2), ATP synthase subunit alpha (ATP5A1) and succinyl‐CoA synthetase subunit beta (SUCLG2). In summary, these results help to develop an understanding of the molecular mechanisms associated with low‐motility sperm and provide clues for finding molecular markers associated with sperm motility.